A call for research on immigrant and refugee youth amidst the global rise in xenophobia and nationalism. (September 2022) - Roche, Kathleen M.; Streitwieser, Bernhard; Schwartz, Seth J.
Abstract: This article describes global shifts in migration and population demography and the simultaneous increase in nationalism and xenophobia. The literature lays out a need for more research examining how young people from immigrant or refugee backgrounds are being affected by contemporary trends in nationalism and xenophobia across diverse national contexts. This article concludes with an overview of five papers addressing the topic in the special section.